Legal Reform and Mediation in Non-Litigation Dispute Resolution: A Case Study of Sebambangan Tradition - Sainul; Ali, Zezen Zainul; Jafar, Wahyu Abdul; Sakirman (Journal of Law and Legal Reform, 2025)
Dispute resolution in indigenous communities tends to be based on family values. This is evident in the Sebambangan tradition where a man elopes with a girl and marries her as his wife. In these cases, dispute resolution is done through mediation (non-litigation) as it is considered more effective for creating harmonization, avoiding conflict, and justice. This research examines the process of non-litigation dispute resolution, namely mediation, in the tradition. This study is a qualitative study using a socio-legal approach. The study was conducted in the Mergo Sekampung indigenous community in East Lampung. Data were collected through observation and interviews with traditional leaders in five villages. The research findings show that the mediation process in the tradition begins with the male party apologizing for the mistakes made. This process is carried out in deliberation and is accompanied by traditional leaders as mediators. Mediation in Sebambangan is part of the living law that prioritizes kinship in dispute resolution. In positive law, the mediation process in the tradition of the Sekampung Marga community in East Lampung follows the material legal basis in Indonesia as in Article 1338 of the Civil Code and Articles 1851 to 1864 of the Civil Code concerning Peace. Thus, dispute resolution in the Sebambangan tradition makes it an alternative dispute resolution in a conflict carried out with family principles to achieve peace and contribute to legal reform in Indonesia and beyond.